Non-target-Site Resistance in Lolium spp. Globally: A Review - Suzukawa, Andréia K.; Bobadilla, Lucas K.; Mallory-Smith, Carol; Brunharo, Caio A. C. G. (Frontiers in Plant Science, 2021)
The Lolium genus encompasses many species that colonize a variety of disturbed and non-disturbed environments. Lolium perenne L. spp perenne, L. perenne L. spp multiflorum, and L. rigidum are of particular interest to weed scientists because of their ability to thrive in agricultural and non-agricultural areas. Herbicides are the main tool to control these weeds; however, Lolium spp. populations have evolved multiple- and cross-resistance to at least 14 herbicide mechanisms of action in more than 21 countries, with reports of multiple herbicide resistance to at least seven mechanisms of action in a single population. In this review, we summarize what is currently known about non-target-site resistance in Lolium spp. to acetyl CoA carboxylase, acetohydroxyacid synthase, microtubule assembly, photosystem II, 5-enolpyruvylshikimate-3-phosphase synthase, glutamine synthetase, very-long chain fatty acids, and photosystem I inhibitors. We suggest research topics that need to be addressed, as well as strategies to further our knowledge and uncover the mechanisms of non-target-site resistance in Lolium spp.